Analisis Morfologi Permukiman Di Kabupaten Bolaang Mongondow Selatan - Ade Dinda Daumpung; Rieneke Sela; Papia Franklin (Universitas Sam Ratulangi, 2021)
Land needs for the construction of settlements, infrastructure and facilities, other needs make the intensity of development to increase, so that there is a change in land use in a region. In 2008, Bolaang Mongondow Regency was born from the expansion of Bolaang Mongondow Regency. Along with the development of settlements that occur, thus causing changes in land use towards lowland, coastal and even hills. Research conducted to look at the morphology of residential land use, covering aspects of land use, road and building networks. The purpose of the study was to identify the development of residential areas and analyze the morphological form of settlements on the coast of South Bolaang Mongondow Regency. This research uses qualitative descriptive method and spatial analysis using ArcGIS 10.7 application. A technique in processing multiple counts and mathematical evaluations is called spatial analysis. The results of land use analysis in South Bolaang Mongondow Regency dominated by land was not built by 99% of the area. Settlement development in a period of 6 years amounted to 105.89 ha or 0.85% of the area. The morphological form of settlements in Bolaang Mongondow Selatan Regency is dominated by morphology along the coastal area along 73.09 ha, while the morphology of the land direction is found in Bolaang Uki District, Pinolisian District, Central Pinolisian District and East Pinolisian District of 136.77 Ha. Morphological forms of settlements in hilly areas are found in Pinolosian subdistrict and East Pinolosian District. Keywords: Morphology, Coastal, Settlement